Adalimumab combined with ciprofloxacin is superior to adalimumab monotherapy in perianal fistula closure in Crohn's disease: a randomised, double-blind, placebo controlled trial (ADAFI). Issue 2 (23rd March 2013) - Dewint, Pieter; Hansen, Bettina E; Verhey, Elke; Oldenburg, Bas; Hommes, Daniel W; Pierik, Marieke; Ponsioen, Cyriel I J; van Dullemen, Hendrik M; Russel, Maurice; van Bodegraven, Ad A; van der Woude, C Janneke
Abstract : Objective: To assess whether a combination of adalimumab and ciprofloxacin is superior to adalimumab alone in the treatment of perianal fistulising Crohn's disease (CD). Design: Randomised, double-blind, placebo controlled trial in eight Dutch hospitals. In total, 76 CD patients with active perianal fistulising disease were enrolled. After adalimumab induction therapy (160/80 mg week 0, 2), patients received 40 mg every other week together with ciprofloxacin 500 mg or placebo twice daily for 12 weeks. After 12 weeks, adalimumab was continued. Follow-up was 24 weeks. Primary endpoint (clinical response) was defined as 50% reduction of fistulas from baseline to week 12. Secondary endpoints included remission (closure of all fistulas), Perianal Crohn's Disease Activity Index, Crohn's Disease Activity Index (CDAI) and Inflammatory Bowel Disease Questionnaire (IBDQ). Results: Clinical response was observed in 71% of patients treated with adalimumab plus ciprofloxacin and in 47% treated with adalimumab plus placebo (p=0.047). Likewise, remission rate at week 12 was significantly higher (p=0.009) in the combination group (65%) compared with adalimumab plus placebo (33%). Combination treatment was associated with a higher mean CDAI change and mean IBDQ change at week 12 (p=0.005 and p=0.009, respectively). At week 24, no difference in clinical response between the two treatment groups was observed (p=0.22). No difference in safety issues was observed. Conclusions: Combination therapy of adalimumab and ciprofloxacin is more effective than adalimumab monotherapy to achieve fistula closure in CD. However, after discontinuation of antibiotic therapy, the beneficial effect of initial coadministration is not maintained. Trial registration: ClinicalTrials.gov Identifier: NCT00736983 .